Tingkat Kesejahteraan Berdasarkan Proporsi Konsumsi Pangan Petani Plasma Kelapa Sawit di Desa Pangkalan Tiga Kecamatan Pangkalan Lada Kabupaten Kotawaringin Barat - Novi Nurhayati (Rawa Sains: Jurnal Sains STIPER Amuntai, 2016)
This study intends to discover the level of household welfare smallholder oil palm in Pangkalan Tiga Village Pangkalan Lada District Kotawaringin Barat Regency. The proportion of food consumption is one indicator to determine the level of household welfare. This study uses primary data and secondary data. Primary data collected include household characteristic smallholder oil palm, food and non food consumption expenditures, farmers income smallholder oil palm, and a land area of plasma and non plasma. Secondary data derived from relevant agencies such as BPS, KP2KP, BPP Pangkalan Lada District, Departement of Agriculture and Animal Husbandry. The data obtained from the field is processed in the from of tabulation and is calculated using the formula PKP. The results showed that based on the level of welfare of farmers based on the proportion of food comsumption 39 farmer households, or about 90,7% of the total sample of households in the category of prosperous farmers and 4 household or about 9,3% in the category of underprivileged